Household coping strategies and food security in the multi-shock environment of Mali - Ulimwengu, John M. (International Food Policy Research Institute, 2025)
This study investigates household coping strategies and food security outcomes within the context of multiple, overlapping shocks, including conflict, food price volatility, climate events, and economic instability. Utilizing a unique household dataset on Mali combined with probit models to account for the compounded effects of these systemic shocks, the analysis highlights significant elasticities between specific shocks and household responses. Key findings demonstrate that while preventive measures, such as income diversification, strengthen resilience, reactive strategies like selling productive assets or borrowing money or food provide only short-term relief but undermine long-term sustainability. The impact of coping strategies on food security measures, including the Food Consumption Score (FCS), Household Dietary Diversity Score (HDDS), and Household Hunger Scale (HHS), reveals the trade-offs Malian households make between immediate needs and future stability. The study emphasizes the critical role of policy interventions in mitigating these vulnerabilities, including strengthening social safety nets, expanding access to financial services, and promoting climate-resilient agricultural practices. By integrating the analysis of multiple shocks, this research provides actionable insights for building household and community resilience in environments of compounded risk.